Mewujudkan Kasih Kristus dalam Keberagaman Agama: Pendekatan Teologi Agama-Agama - Ester Widiyaningtyas; Eirene Victoria Sele Barail; Resa Junias (Journal Of Spirituality And Practical Theology, 2025)
Religious diversity is a social and theological reality that demands contextual and transformative reflection of Christian faith. This article aims to explore how Christ's love can be realized in a pluralistic life together through the approach of theology of religions. Using qualitative-reflective methods and literature studies, this study examines three main approaches in theology of religions, namely exclusivism, inclusivism, and pluralism, and their implications in building interfaith relations. The love of Christ, which is universal and transformative, becomes the ethical and spiritual foundation in presenting sincere, just, and peaceful interfaith dialogue. This article concludes that amidst the complexity of pluralism, the church and Christians are called to bear witness with active love, which not only respects differences, but also brings about restoration and social justice. This research is expected to provide a theological contribution to the development of a more inclusive paradigm of interfaith relations based on divine love.